High Neutrophil–Lymphocyte Ratio Predicts Post-stroke Cognitive Impairment in Acute Ischemic Stroke Patients - Lee, Minwoo; Lim, Jae-Sung; Kim, Chul-Ho; Lee, Sang-Hwa; Kim, Yerim; Hun Lee, Ju; Jang, Min Uk; Sun Oh, Mi; Lee, Byung-Chul; Yu, Kyung-Ho (Frontiers in Neurology, 2021)
Background and Aims Systemic inflammation is associated with an increased risk of cognitive impairment and dementia, but the associations between them in stroke patients are less clear. We examined the impact of systemic inflammation represented as the neutrophil-lymphocyte ratio(NLR) on the development of post-stroke cognitive impairment(PSCI) and domain-specific cognitive outcomes 3-month after ischemic stroke. Methods Using prospective stroke registry data, we consecutively enrolled 345 participants with ischemic stroke whose cognitive functions were evaluated 3-month after stroke. Their cognition was assessed with the Korean version of the Vascular Cognitive Impairment Harmonization Standards and the Korean-Mini Mental Status Examination. PSCI was defined as a z-score of less than -2 standard deviations for age, sex, and education adjusted means in at least one cognitive domain. The participants were categorized into five groups according to the quintiles of NLR(lowest NLR, Q1). The cross-sectional association between NLR and PSCI was assessed using multiple logistic regression, adjusting for age, sex, education, vascular risk factors, and stroke type. Results A total of 345 patients were enrolled. The mean age was 63.0 years and the median NIHSS score and NLR were 2[1-4] and 2.26[1.65-2.91], respectively. PSCI was identified in 71(20.6%) patients. NLR was a significant predictor for PSCI both as a continuous variable (adjusted OR, 1.14; 95% CI, 1.00-1.31) and as a categorical variable (Q5, adjusted OR, 3.26; 95% CI, 1.17-9.08). Patients in the Q5 group (NLR ≥3.80) showed significantly worse performance in global cognition and in visuospatial and memory domains. Conclusions NLR in the acute stage of ischemic stroke was independently associated with PSCI at 3 months after stroke, and high NLR was specifically associated with cognitive dysfunction in the memory and visuospatial domains. Thus, systemic inflammation may be a modifiable risk factor that may influence cognitive outcomes after stroke.